Yoga Pandita Texts And Contexts In Griyas Buleleng Regency - Luh Asli (Institut Hindu Dharma Negeri Denpasar, 2020)
Yoga is increasingly more favorite among a large part of communities of the world crossing religious and cultural backgrounds It has become a lifestyle because of the benefits that the people who practice it. It is one of the spiritual assets and wisdoms of Hinduism offered to the world, not only in India, but also in Bali, both in terms of text and context. A number of texts in Bali contain theories and practices of what is called Yoga Pandita. The sources of this type are found and actualized within griyas. Actually, people havee taught Yoga Pandita since the emergence of griyas in Bali. Griya is a place in Bali where traditional Hinduism education takes place. A number ot texts such as Silakrama, Wrspati Tatwa, Sivasasana, Ganapati Tatwa are used as guides in actualizing yoga within the griyas. Most of the practices of Yoga Pandita in the griya areas especially in those in Buleleng regency tend to practice samyama or Raja Yoga and only a small part practices Hatha Yoga. This is caused by the factors such as age, degradation in physical ability , however in terms of mental ability and mind control and spirituality the people who practice yoga increasily more stable. This is a ladder in the esoteric world and is relevant in making progress of Astanggayoga in Patanjali Yogasutra.